2019
DOI: 10.1002/jobm.201800490
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of fenpropathrin by Rhodopseudomonas sp. strain PSB07‐21 cultured under three different growth modes

Abstract: This study aimed at the biodegradation of fenpropathrin by Rhodopseudomonas sp. strain PSB07‐21 cultured under different growth modes. The biomass production, cell surface hydrophobicity and fenpropathrin biodegradation efficiency of the strain PSB07‐21 cultured under the photoheterotrophic growth mode were better than that shown by the strain PSB07‐21 cultured under the photoautotrophic or the chemotrophic growth mode. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis analysis using cell‐free protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Detailed metabolic pathway of fenpropathrin biodegradation through strain pyd-1 was also identified. Specific enzyme activities of pyrethroid hydrolase, 3-phenoxybenzaldehyde (PBD) dehydrogenase, 3-phenoxybenzoic acid (PBA) hydroxylase, 4-hydroxy-PBA dioxygenase, and p-hydroquinone hydroxylase have been studied in relation to pyrethroid fenpropethrin (Dehmel et al, 1995; Wang et al, 2011; Luo et al, 2019). Pseudomonas pseudoalcaligenes strain POB310 has been reported for the degradation of 3- and 4-carboxydiphenyl ethers (Dehmel et al, 1995).…”
Section: Pyrethroid-degrading Microorganisms and Their Degradation Chmentioning
confidence: 99%
“…Detailed metabolic pathway of fenpropathrin biodegradation through strain pyd-1 was also identified. Specific enzyme activities of pyrethroid hydrolase, 3-phenoxybenzaldehyde (PBD) dehydrogenase, 3-phenoxybenzoic acid (PBA) hydroxylase, 4-hydroxy-PBA dioxygenase, and p-hydroquinone hydroxylase have been studied in relation to pyrethroid fenpropethrin (Dehmel et al, 1995; Wang et al, 2011; Luo et al, 2019). Pseudomonas pseudoalcaligenes strain POB310 has been reported for the degradation of 3- and 4-carboxydiphenyl ethers (Dehmel et al, 1995).…”
Section: Pyrethroid-degrading Microorganisms and Their Degradation Chmentioning
confidence: 99%
“…A exposição crônica ou a bioacumulação de alguns piretróides como a detectada neste estudo, a fenpropatrina, pode provocar toxicidade neuro comportamental em mamíferos (Liu et al, 2015). Além da não recomendação do uso deste pesticida no cultivo da batata, a detecção da presença deste agrotóxico no efluente resulta em um grave problema ambiental, visto que os piretróides são extremamente tóxicos no ambiente aquático (Luo et al, 2019). A Fenpropatrina no sistema aquático dissipa-se rapidamente da fase aquosa dissolvida e liga-se ao carbono orgânico em partículas de sedimentos (Fojut;Young, 2011).…”
Section: Resultsunclassified
“…During poultry excreta treatment microbes of Rhodopseudomonas sp., and Pseudomonas fluorescens present in FMC role was important because several species of Rhodopseudomonas sp., have been demonstrated to have the ability to degrade various synthetic pyrethroids, and DDVP. Luo et al, [62] reported encoding genes of 2OG-Fe(II) oxygenase enzyme of Rhodopseudomonas sp. PSB07-21 having capability of degrading synthetic pyrethroids.…”
Section: Discussionmentioning
confidence: 99%